Hormonal Contraceptive Use, Neuromuscular Performance, and Musculoskeletal Health During Military Training - Jenna Blair Goulart; Jennifer N. Forse; Evan D Feigel; Matthew B Bird; Elizabeth J Steele; Ayden M McCarthy; Mita Lovalekar; Brian J. Martin; Bradley C. Nindl; Kristen J Koltun (Applied Physiology, Nutrition, and Metabolism, 2026)
Despite data showing half of active-duty servicewomen use hormonal contraception, its impact on physical performance during military training remains unclear. This study examined differences in general and military-specific physical performance and bone health changes based on hormonal contraceptive use. 185 female Marine Officer Candidates (MOCs) were grouped by self-reported menstrual/hormonal contraceptive status. Questionnaires, countermovement jumps (CMJ), isometric mid-thigh pull (IMTP), physical fitness tests (PFT), peripheral Quantitative Computed Tomography (pQCT; 4%, 38%, 66% tibia length), and bone biomarkers were assessed at the start and end of the 10-week program. A combat fitness test (CFT) was completed during training. Mixed ANOVAs (group*time) assessed training responses. Among 104 MOCs not using hormonal contraception (Non-Users; age=25[IQR; 22, 27], BMI=23.98±1.98) and 81 MOCs using hormonal contraception (Users; age=24[IQR; 22,26], BMI=23.97±2.19), Users showed no change in CMJ reactive strength index, while Non-Users decreased (interaction p=0.042; Non-Users Δ= -0.03, p